Advanced students' knowledge of vocabulary in a first and second language - Karlsson, Monica 1966- (Second language acquisition, 2022)
This book offers a comprehensive investigation into advanced students' knowledge of vocabulary in their L1 and L2. This cross-sectional study examines the qualitative and quantitative aspects of students' vocabulary knowledge in subfields such as suffixation, idioms and proverbs, multi-word verbs, polysemous words and inferencing skills